All Days 1994
DOI: 10.2118/27607-ms
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical Controls on Inhibitor Adsorption/Desorption in Brent Group Sandstone and Their Importance in Predicting and Extending Field Squeeze Lifetimes

Abstract: The problem of downhole mineral scale formation is most commonly remedied by carrying out scale inhibitor "squeeze" treatments. The success of this process depends on there being an appropriate level of interaction between the scale inhibitor species and the rock formation. This interaction is described by an adsorption isotherm, F(C), in adsorption/desorption type squeeze treatments and the nature of this isotherm governs the dynamics of the inhibitor return profile. The isotherm depends on the factors relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…However, it was demonstrated that presence of Ca 2+ plays an important role in adsorption of SI on rock [79]. In addition, kaolinite has been shown to facilitate adsorption of inhibitors onto the rock [80]. It is concluded that PPCA does not have a tendency to react with silica in DW, but on the other hand it has a propensity to bond with CNTs.…”
Section: Results Of Nast2mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was demonstrated that presence of Ca 2+ plays an important role in adsorption of SI on rock [79]. In addition, kaolinite has been shown to facilitate adsorption of inhibitors onto the rock [80]. It is concluded that PPCA does not have a tendency to react with silica in DW, but on the other hand it has a propensity to bond with CNTs.…”
Section: Results Of Nast2mentioning
confidence: 99%
“…The entire NAST procedure was applied step by step, and results are compared with baseline corefloods using a current standard procedure [80] in which no CNTs were used. Figure 12 illustrates the SI concentration at outlet of cores for standard and NAST coreflood tests.…”
Section: Coreflood Resultsmentioning
confidence: 99%
“…It has been reported that in adsorption/desorption squeeze treatment applications, the nature of the isotherm depicts the behavior of the inhibitor return profile [75]. Reports have depicted that the nature of adsorption isotherm is influenced by (i) inhibitor species itself, (ii) the formation brine composition and pH, (iii) application pH and temperature, and (iv) the nature of adsorbing surface, i.e., surface charge, reservoir mineralogy, and wettability [62,75]. Bassioni [76] maintained that electrostatic interaction by means of ionpair formation, ion exchange, hydrogen bonding, or complex formation on the surface of formation rock with saturated adsorption plateau gives rise to adsorption.…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…At equilibrium, the concentration of the solute or adsorbate in the bulk liquid to the concentration of the adsorbate on the solid phase defines the adsorption isotherm (Salvaraju and Pushpavanam, 2009). It has been reported that in adsorption/desorption squeeze treatment applications, the nature of the isotherm depicts the behaviour of the inhibitor return profile (Jordan et al, 1994). Reports have depicted that the nature of adsorption isotherm is influenced by (i) inhibitor species itself, (ii) the formation brine composition and pH, (iii) application pH and temperature and (iv) the nature of adsorbing surface i.e.…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…Reports have depicted that the nature of adsorption isotherm is influenced by (i) inhibitor species itself, (ii) the formation brine composition and pH, (iii) application pH and temperature and (iv) the nature of adsorbing surface i.e. surface charge, reservoir mineralogy and wettability (Jordan et al, 1994;Vazquez et al, 2011). Bassioni (2010) maintained that electrostatic interaction by means of ion-pair formation, ion exchange, hydrogen bonding or complex formation on the surface of formation rock with saturated adsorption plateau gives rise to adsorption.…”
Section: Adsorption Isothermmentioning
confidence: 99%